2004
DOI: 10.1159/000080283
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Diagnosis and Treatment Results in 106 Patients with Uterine Sarcoma in Hokkaido, Japan

Abstract: Objective: The aim of this study was to evaluate the clinicopathological features of uterine sarcoma in Hokkaido, Japan, between 1990 and 1999, and to identify prognostic factors of patients with such malignancies in this area and period. Methods: One hundred and six patients with histologically proven uterine sarcoma were evaluated retrospectively. Results: 93.5% of the patients with carcinosarcoma (CS) were diagnosed as having malignant disease preoperatively, while 65% of those with leiomyosarcoma (LMS) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
88
0
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(105 citation statements)
references
References 23 publications
11
88
0
6
Order By: Relevance
“…S o m e s t u d i e s r e p o r t e d t h a t t u m o r g r a d e (Ghaemmaghami et al, 2008), tumor size (George et al, 1986;Rovirosa et al, 2002;Benito et al, 2009), depths of myometrial invasion (Rovirosa et al, 2002;Sagage et al, 2004;Park et al, 2008), LVSI (Major et al, 1993;Rovirosa et al, 2002;Park et al, 2008) had significant effect on prognosis of uterine sarcomas. In our study grade had significant effecet on RFS and OS.…”
Section: 1935 Prognostic Factors and Treatment Outcomes In Patients mentioning
confidence: 99%
“…S o m e s t u d i e s r e p o r t e d t h a t t u m o r g r a d e (Ghaemmaghami et al, 2008), tumor size (George et al, 1986;Rovirosa et al, 2002;Benito et al, 2009), depths of myometrial invasion (Rovirosa et al, 2002;Sagage et al, 2004;Park et al, 2008), LVSI (Major et al, 1993;Rovirosa et al, 2002;Park et al, 2008) had significant effect on prognosis of uterine sarcomas. In our study grade had significant effecet on RFS and OS.…”
Section: 1935 Prognostic Factors and Treatment Outcomes In Patients mentioning
confidence: 99%
“…Yamawaki et al (6) reported that IAP was effective in a case with progressive UES. Yamaguchi et al (23) also reported that the rate of PR with IAP therapy for uterine sarcomas was 40.0% in the first-line and 9.1% in the second-line chemotherapy setting.…”
Section: Discussionmentioning
confidence: 99%
“…High-grade ESS, in particular, is referred to as undifferentiated endometrial sarcoma (UES). Total hysterectomy and bilateral salpingo-oophorectomy (BSO) are currently considered the first choice for the treatment of uterine sarcomas, although a consensus has not been reached regarding retroperitoneal lymphadenectomy (5,6). However, these tumors cannot be sufficiently controlled by surgical treatment alone, since a number of patients develop progression and recurrence of uterine sarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…In the Japanese population, 13-19% of these tumors are classified as endometrial stromal sarcoma (ESS) (2,3). Due to the changes in the World Health Organization classification in 2003, which classified high-grade ESS as undifferentiated endometrial sarcoma (4), low-grade ESS (LG-ESS) may simply be referred to as ESS in some cases, although the classification reverted to its original form in 2014 (5).…”
Section: Introductionmentioning
confidence: 99%